Empat Pilar Biofisika dalam Keperawatan untuk Peningkatan Mutu Asuhan - Zurni Faulina; Alysia Ivanda Candra Ramadhani; Widia Nur Fatimah; Tasbita Anit Sulastri; Aula Nafit; Zahra Adinda Prabawati Sulendro; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
The advancement of medical technology and patient safety demands the incorporation of biophysical principles into everyday nursing practice. This literature review synthesizes the roles of four biophysical pillars biomechanics, bioelectricity, thermophysics, and biofluid dynamics in nursing actions relevant to care quality. Biomechanics is applied in nurse ergonomics and patient mobilization, bioelectricity in vital sign monitoring (e.g. ECG, defibrillation) and electrotherapy safety, thermophysics in thermal regulation via conduction, convection, radiation, and evaporation, biofluid dynamics in IV fluid management, hemodynamic interpretation, and respiratory gas flow. From recent studies, mastery of these biophysical principles significantly enhances clinical accuracy, reduces musculoskeletal injuries among nurses, and accelerates patient recovery. It is recommended that nursing education institutions integrate practical biophysics modules via simulation and clinical laboratory practice.